MOF‐Based Hierarchical Structures for Solar‐Thermal Clean Water Production. Issue 17 (11th March 2019) - Ma, Qinglang; Yin, Pengfei; Zhao, Meiting; Luo, Zhiyong; Huang, Ying; He, Qiyuan; Yu, Yifu; Liu, Zhengqing; Hu, Zhaoning; Chen, Bo; Zhang, Hua
Abstract: Solar‐thermal water evaporation, as a promising method for clean water production, has attracted increasing attention. However, solar water evaporators that exhibit both high water vapor generation ability and anti‐oil‐fouling ability have not been reported. Here, a unique metal–organic‐framework‐based hierarchical structure, referred to as MOF‐based hierarchical structure (MHS), is rationally designed and prepared, which simultaneously displays a high solar absorption and a superhydrophilic and underwater superoleophobic surface property. As a proof‐of‐concept application, a device prepared from the MHS can achieve a high solar‐thermal water evaporation rate of 1.50 kg m −2 h −1 under 1 sun illumination. Importantly, the MHS also possesses an excellent anti‐oil‐fouling property, ensuring its superior water evaporation performance even in oil‐contaminated water. The high solar‐thermal water evaporation rate and anti‐oil‐fouling property make the MHS a promising material for the solar‐thermal water production. Abstract : The first metal–organic framework (MOF)‐based solar–thermal water evaporator is designed and fabricated with a unique hierarchical structure, which simultaneously enhances the light absorbance and promotes the superhydrophilic and underwater superoleophobic property. As a result, a high water evaporation rate is achieved even in oil‐contaminated water.